A Critique of the Book “Visual Design and Communications: Contribution to a Teaching Methodology” - Alireza Taheri; Sahar Sadeghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2020)
Creativity is the most basic ability of the human brain. The artist with visual communication always tries to create great ideas with new ideas. Bruno Monari is an artist and creative innovator. In 1967, Monari initiated innovative experiences and training of interested students at Harvard University and included their experiences, successes, and failures in a book entitled “Visual Design and Communications: Contribution to a teaching methodology”. This article introduces and critically examines the book of Bruno Munari, which was translated by Paiandeh Shahandeh in 2008. The purpose of this article is to express the points to be considered in order to make the work more effective and to introduce more and more of the author’s approach to planning for a complete teaching of visual communication at universities and colleges in the country. The research methodology is descriptive-analytical with a critical approach, and the tools for collecting library data, articles, and Internet resources are valid. The book can be enriched by providing more creative images and pictures, giving them the right logical consistency, and deleting and adding parts of the content to its beneficial coefficient for all those related to visual arts.